Multimodal iron oxide nanoparticles for hybrid biomedical imaging. (15th October 2012) - Heidt, Timo; Nahrendorf, Matthias; Mulder, Willem J. M.; McMahon, Michael T.; Nicolay, Klaas
<x xml:space="preserve">Abstract</x> Iron oxide core nanoparticles are attractive imaging agents because their material properties allow the tuning of pharmacokinetics as well as the attachment of multiple moieties to their surface. In addition to affinity ligands, these include fluorochromes and radioisotopes for detection with optical and nuclear imaging. As the iron oxide core can be detected by MRI, options for combining imaging modalities are manifold. Already, preclinical imaging strategies have combined noninvasive imaging with higher resolution techniques, such as intravital microscopy, to gain unprecedented insight into steady‐state biology and disease. Going forward, hybrid iron oxide nanoparticles will help to merge modalities, creating a synergy that will enable imaging in basic research and, potentially, also in the clinic. Copyright © 2012 John Wiley & Sons, Ltd.